Multiple Minor QTLs Are Responsible for Fusarium Head Blight Resistance in Chinese Wheat Landrace Haiyanzhong - Cai, J.; Wang, S.; Li, T.; Zhang, Guorong R.; Bai, Guihua H. (My University, 2016)
Fusarium head blight (FHB), caused by Fusarium graminearum Schwabe, is a devastating disease in wheat (Triticum aestivum L.). Use of host resistance is one of the most effective strategies to minimize the disease damage. Haiyanzhong (HYZ) is a Chinese wheat landrace that shows a high level of resistance to FHB spread within a spike (type II resistance). To map the quantitative trait loci (QTLs) in HYZ and identify markers tightly linked to the QTLs for FHB resistance, a population of 172 recombinant inbred lines (RILs) from a cross between HYZ and Wheaton (FHB susceptible) was genotyped using simple sequence repeats (SSRs) and single-nucleotide polymorphisms (SNPs) derived from genotyping-bysequencing (GBS), and evaluated for percentage of symptomatic spikelets (PSSs) per spike in three greenhouse experiments. Six QTLs for type II resistance were identified in HYZ, indicating that multiple minor QTLs together can provide a high level of FHB resistance in wheat. The QTL with the largest effect on FHB resistance was mapped on the chromosome arm 5AS, and the other five from HYZ were mapped on the chromosomes 6B, 7D, 3B, 4B and 4D. In addition, two QTLs from Wheaton were mapped on 2B. Critical SNPs linked to the QTLs on chromosomes 5A, 6B, and 2B were converted into KBioscience competitive allele-specific PCR (KASP) assays, which can be used for marker-assisted selection (MAS) to pyramid these QTLs in wheat
Citation: Cai, Jin, Shan Wang, Tao Li, Guorong Zhang, and Guihua Bai. “Multiple Minor QTLs Are Responsible for Fusarium Head Blight Resistance in Chinese Wheat Landrace Haiyanzhong.” Edited by Maoteng Li. PLOS ONE 11, no. 9 (September 27, 2016): e0163292. https://doi.org/10.1371/journal.pone.0163292.
Keywords: Quantitative Trait Loci; Triticum-Aestivum L.; Marker-Assisted; Selection; X Wangshuibai Population; Spring Wheat